Bilderbuch : Documenta Kassel 16/06-23/09 2007 (Kassel : Documenta und Museum Fridericianum Veranstaltungs GmbH Kassel, 2007)
Friedl, Peter ; Frisson, Geneviève ; Geyer, Andrea ; Hallett, George ; Linke, Armin ; Nevidal, Hans ; Osodi, George ; Riera, Alejandra ; Rosler, Martha ; Sekula, Allan ; Spiluttini, Margherita ; Trogemann, Egbert ; de Ven, Lidwien van ; Woodman, Edward
Duits
Exhibition. documenta 12. stad Kassel. Documenta Archiv Kassel. 2007-06-16. 2007-09-23
boek